2018
DOI: 10.1007/s00405-018-5162-6
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of hyperbaric oxygen in patients with idiopathic sudden sensorineural hearing loss: a systematic review

Abstract: ObjectiveTo evaluate the effectiveness of hyperbaric oxygen in the treatment of patients with idiopathic sudden sensorineural hearing loss (ISSHL).Data sourcesAn Embase, MEDLINE and Cochrane search were utilised to identify various clinical trials on the treatment of ISSHL. Studies that were published between 2002 and 2018 and written in the English, Dutch or German language were included. Search terms included synonyms for idiopathic sudden hearing loss.Data synthesisA total of 16 articles were identified reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 37 publications
4
39
0
Order By: Relevance
“…Therefore, although we found no difference between the two groups, we believe that HBO should be considered as a treatment strategy in this patient group, especially for severe and profound hearing loss. In a review conducted in 2018, it was reported that adding HBO to steroid treatment may be beneficial in cases of severe and profound hearing impairment [22]. The guideline for clinical practice for ISSHL, which was updated this year, states that HBO can be administered as the initial therapy in combination with steroids within the first two weeks of onset, or as salvage therapy within the first month [23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although we found no difference between the two groups, we believe that HBO should be considered as a treatment strategy in this patient group, especially for severe and profound hearing loss. In a review conducted in 2018, it was reported that adding HBO to steroid treatment may be beneficial in cases of severe and profound hearing impairment [22]. The guideline for clinical practice for ISSHL, which was updated this year, states that HBO can be administered as the initial therapy in combination with steroids within the first two weeks of onset, or as salvage therapy within the first month [23].…”
Section: Discussionmentioning
confidence: 99%
“…Standard steroid therapy is the first-line treatment option in SSNHL [5]. The rationale for using corticosteroids for the treatment of SSNHL is based on the hypothesis suggesting that steroids can prevent or reverse the inflammation in the internal ear [12].…”
Section: Discussionmentioning
confidence: 99%
“…Even though great heterogeneity exists between the definition of ‘complete recovery’ in different studies, HBOT was superior to MT in terms of complete recovery in the majority of studies (12 out of 14) [ 146 ]. Other authors (Eryigit, Saesen, Murphy-Lavoie) have also published reviews on the use of HBOT in ISSHL [ 27 , 147 , 148 ]. Their conclusions were mostly positive, especially showing results in favor of HBOT in patients with severe and profound hearing loss.…”
Section: Clinical Use Of Hyperbaric Oxygen Therapymentioning
confidence: 99%
“…However, according to the Cochrane Library, no other specific drug therapy has been documented to be proven effective against hearing loss in case of AAT or ISSHL. In recent years, HBOT has been used for AAT and ISSHL by many colleagues; however due to the lack of randomized controlled trials, it is still unclear what the role of HBOT should be in the treatment protocol of these two types of acute hearing loss [ 27 ]. This narrative review provides the rationale and evidence for HBOT in AAT and ISSHL.…”
Section: Introductionmentioning
confidence: 99%